Investigating human paleodiet at Mesolithic Yuzhniy Oleniy Ostrov, Karelia using a multi-proxy stable isotope approach - Rebekka I. I. Eckelmann; Laura Arppe; Rick J. Schulting; Sambit Ghosh; Jakub Trubač; Aneta Kuchařová; Matthew J. Wooller; Dmitry Gerasimov; Vyacheslav Moiseyev; Kristiina Mannermaa (PLoS ONE, 2026)
This study employs multiple isotopic proxies to investigate dietary practices at Yuzhniy Oleniy Ostrov (YOO, Karelia, north-western Russia), the largest Mesolithic cemetery in northern Europe. Building on previous research, we combine bulk δ ¹³C and δ ¹⁵N collagen measurements from 60 human individuals with new δ ¹³C values on enamel bioapatite (n = 10) and the first archaeological compound-specific isotope analysis of amino acids (CSIA-AA) from north-western Russia (n = 6), to provide a more comprehensive view of local resource use and dietary patterns. Results show that YOO forms a distinct isotopic cluster within the broader circum-Baltic hunter-gatherer-fisher spectrum, characterized by unusually high δ ¹⁵N values for an inland site. CSIA-AA and combined enamel-collagen δ ¹³C data do not indicate marine contributions or freshwater seal hunting as the drivers of these values, instead confirming a high reliance on freshwater resources compatible with the Lake Onega system and potentially an increased diet-to-tissue offset related to a high protein diet. FRUITS Bayesian dietary modelling similarly indicated a high freshwater component, alongside unexpectedly low contributions from terrestrial game and high estimates for plant foods. The latter results diverge from ethnographic expectations for boreal hunter-gatherer-fisher subsistence and may reflect current limitations in modelling lipid intake and adaptive strategies in high-protein diets, highlighting a need to reconsider how isotopic and ethnographic data are integrated. Isotopic variability between individuals was minimal, with no significant differences by sex or burial location, supporting a shared dietary regime during the relatively short period of site use. Overall, this study presents the most detailed isotopic evaluation of diet at Yuzhniy Oleniy Ostrov to date and underscores the value of multi-proxy isotope analysis in exploring prehistoric lifeways.